Long-term outcomes of patients with breast cancer after nipple-sparing mastectomy/skin-sparing mastectomy followed by immediate transverse rectus abdominis musculocutaneous flap reconstruction: Comparison with conventional mastectomy in a single center study. Issue 18 (May 2018) - Lee, Sae Byul; Lee, Jong Won; Kim, Hee Jeong; Ko, Beom Seok; Son, Byung Ho; Eom, Jin Sup; Lee, Taik Jong; Ahn, Sei-Hyun
Abstract : Abstract: To evaluate the oncological outcomes of patients with breast cancer after nipple-sparing mastectomy (NSM)/skin-sparing mastectomy (SSM), followed by immediate reconstruction, as compared to conventional mastectomy (CM). SSM/NSM has been increasingly used to treat women with breast cancer who wish to preserve the overlying breast skin, but concern exist regarding its oncological safety due to the potential for residual breast tissue. We report our experience performing SSM/NSM for breast cancer treatment compared to CM with a long follow-up period. All consecutive patients who underwent mastectomy for breast cancer at Asan Medical Center between January 1993 and December 2008 were identified by retrospective medical chart review. The patients who underwent NSM/SSM, followed by immediate breast reconstruction with a pedicled transverse rectus abdominis musculocutaneous flap (TRAM), were compared to the patients who underwent CM in terms of breast-cancer specific survival (BCSS) rate, distant metastasis-free survival (DMFS) rate, and local recurrence (LR) rate. During the study period, 6028 patients underwent mastectomy for breast cancer. Of these, 1032 and 4996 underwent NSM/SSM with TRAM and CM, respectively. Their median follow-up durations were 94.4 (range, 8.1–220.2) and 110.8 (range, 6.1–262.0) months, respectively. Their 5 year BCSS rates were 95.4% and 88.1%, respectively (log-rank, P <  .001). Their 5 year DMFS rates were 93.0% and 85.6%, respectively (log-rank, P <  .001). Relative to CM, NSM/SSM, followed by immediate breast reconstruction, may be a viable and oncologically safe surgical treatment in selected patients with breast cancer. Abstract : Supplemental Digital Content is available in the text